Translation Quality Assessment on Medan City Tourism Official Web Pages - Putri, Ruth Suci; Sofyan, Rudy; Nasution, Ely Hayati (LingPoet: Journal of Linguistics and Literary Research, 2022)
This research was conducted to analyze the quality of the translation on the Medan City Tourism web pages. In this research, the researcher used the translation quality assessment model proposed by Nababan et al. The TQA model by Nababan et al. focuses on three aspects, namely accuracy, acceptability, and readability. The final result of measuring these three aspects is the total value for the quality of the translation on a scale of 1-3. This research has the objectives to: 1) analyze the accuracy of the Indonesian- English translation of the Medan Tourism web page 2) to analyze the acceptability of the Indonesian-English translation of the Medan Tourism web page 3) to analyze the readability of the Indonesian-English translation of the Medan Tourism web page 4) to analyze the total quality of the Indonesian-English translation of the Medan Tourism web pages. There were three professional translators as the raters who helped in assessing the text of the Medan City Tourism web pages. In general, the results of this research indicate that the translation quality of the Medan City Tourism web page is accurate, quite acceptable, and quite readable. The score for the accuracy aspect is 2.7, for the acceptability aspect is 2.2, for the readability aspect is 2.2 and the total quality of the translation is 2.4.